Financial assessment and risk analysis for airport parking - Anna Sigga Lúðvíksdóttir 1983- (2017)
The increase of passengers to and from Iceland has been enormous last years and that calls for a major restructure at Keflavik Airport. There has been pressure on Isavia, that runs the airport, to improve the parking options at the airport. A proposal for a parking garage at Keflavik Airport has been published. The main purpose of this thesis is to find the most feasible option for Isavia to operate the parking garage. This thesis covers the financial feasibility for short term (10 years) and long term (20 years) with respect to the assumptions in the model. The assumption variables that have the most effects are the predicted initial revenue for first year of operation and the investment cost. Three operation models will be compared, i.e. 1) if Isavia builds and operates the parking garage, 2) if Isavia builds the parking garage but outsources the operation to a contractor and 3) if Isavia outsources the land to a contractor who builds and operates the parking garage. To compare the models, net present value, external rate of return and internal rate of return are calculated for all the operation models. This study is intended as a tool for Isavia to use, for further studies, for this investment project. The variable assumptions can be changed in the model and Isavia can adapt the model to different circumstances and scenarios as applicable. The results give a good image of what operation model is Farþega fjölgun á Keflavíkurflugvelli hefur verið mikil síðastliðin ár. Þessi fjölgun leiðir af sér að mikil uppbygging þarf að eiga sér stað á Keflavíkurflugvelli. Það hefur verið mikill þrýstingur á Isavia, sem rekur flugvöllinn, að bæta bílastæði og bílastæðaþjónustu við flugvöllinn. Tillaga að bílastæðahúsi við Keflavíkur flugvöll hefur verið lögð fram. Markmið rannsóknarinnar er að meta hvaða rekstarlíkan er arðbærast fyrir Isavia við að reka bílastæðahúsið. Rannsóknin fjallar um arðsemi fjárfestingarinnar til skamms tíma (10 ára) og til lengri tíma (20 ára) með tilliti til forsenda í líkaninu. Þær breytilegu ...